Annual report 2016: CGIAR Research Program on Humidtropics - CGIAR Research Program on Integrated Systems for the Humid Tropics (CGIAR Research Program on Integrated Systems for the Humid Tropics, 2017)
Humidtropics was launched in July 2012, as an integrated systems research program, with the goal of improving overall agricultural productivity in a sustainable manner, and transforming the lives of the rural poor in the humid tropics. The program has performed significantly well over the period as judged through the Centre-Commissioned External Evaluation conducted in 2015, and by the various annual assessment reviews on Annual Report and POWB reports.